Final answer:
To prove that the linear combination y(x) = c1y1(x) + c2y2(x) is also a solution to the given linear second-order differential equation, we need to substitute it into the equation and show that it satisfies the equation. By substituting y(x) = c1y1(x) + c2y2(x) into the differential equation, we can simplify and demonstrate that the left-hand side of the equation becomes 0, proving that y(x) = c1y1(x) + c2y2(x) is a solution.
Step-by-step explanation:
In order to prove that the linear combination y(x) = c1y1(x) + c2y2(x) is also a solution to the given linear second-order differential equation, we need to substitute it into the equation and show that it satisfies the equation. Let's substitute y(x) = c1y1(x) + c2y2(x) into the differential equation and simplify:
d^2y/dx^2 + a1(x)dy/dx + a0(x)y = 0
d^2(c1y1(x) + c2y2(x))/dx^2 + a1(x)d(c1y1(x) + c2y2(x))/dx + a0(x)(c1y1(x) + c2y2(x)) = 0
c1(d^2y1/dx^2 + a1(x)dy1/dx + a0(x)y1) + c2(d^2y2/dx^2 + a1(x)dy2/dx + a0(x)y2) = 0
Since both y1(x) and y2(x) are solutions to the differential equation, we know that d^2y1/dx^2 + a1(x)dy1/dx + a0(x)y1 = 0 and d^2y2/dx^2 + a1(x)dy2/dx + a0(x)y2 = 0. Therefore, when we substitute y(x) = c1y1(x) + c2y2(x), the left-hand side of the equation becomes c1(0) + c2(0) = 0. This means that y(x) = c1y1(x) + c2y2(x) is a solution to the given linear second-order differential equation.